The Effectiveness of Change Management in Developing the Organizational Culture of it Darul Azhar - M. Idrus Hasibuan (BIRCU, 2021)
This study aims: 1) How to Planning, Organizing, Monitoring and Implementing Change Management 2) What are the steps of the Principal in developing organizational culture 3) What are the supporting and inhibiting factors of the effectiveness of change management in developing organizational culture at SMP IT Darul Azhar Southeast Aceh. This type of research is qualitative. The approach in this study uses a descriptive approach. As informants in this study were the principal, teachers, and students. Research data collection techniques using observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. Techniques to guarantee data validity are credibility, transferability, dependability, and conformability. The results of this study indicate that there are three most important points in the effectiveness of change management in developing the organizational culture of SMP IT Darul Azhar, namely: In change management, the principal is planning according to the needs of students and then by organizing by dividing tasks to teachers to carry out planning, then supervision, namely to know the progress of this change management. In developing the school principal's organizational culture, namely the implementation of morning apples, dhuha prayers, and tadarus al-qur'an after the midday prayers. The supporting factor is the willingness of teachers and students to be better at applying religious values. The inhibiting factor is the lack of competent human resources (HR), loyal to change.